1951
DOI: 10.1113/jphysiol.1951.sp004566
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the mixtures of acetic, propionic and butyric acids in the rumen and in the blood leaving the rumen

Abstract: Absorption of acetic, propionic and butyric acids is known to occur from the rumen of sheep but some confusion concerning relative rates of absorption of these acids has arisen, for although it is agreed that free acids are absorbed more rapidly than their sodium salts when aqueous solutions are in the rumen (Danielli, Hitchcock, Marshall & Phillipson, 1945;Gray, 1947) it has been claimed recently that no absorption at all occurs from the rumen when the pH is over 7 (Gray, 1948).Under normal feeding conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

1954
1954
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 5 publications
(3 reference statements)
2
34
0
Order By: Relevance
“…Danlelll et al (1945), using the change in the concentration of VFA in the rumen contents as the criterion of absorption, found that the order of absorption of the three principal VFA was as suggested by Barcroft et al (1944a) when the rumen con tents were alkaline (pH 7.5)• However from rumen contents at a more acid reaction (pH 5.8) the higher homologues of the VFA were absorbed faster. Kiddle et al (1951) concluded that the higher homologues of the VFA were not absorbed prefer entially from rumen contents at an acid pH, but Gray et al (1951), Gray and Pilgrim (1951), Hungate et al (1961), Johnson (1951) and Pfander and Phillipson (1953) confirmed the conclusions of Danlelll et al (1945) and Gray (1947Gray ( , 1948.…”
Section: Structure Of the Rumensupporting
confidence: 76%
See 4 more Smart Citations
“…Danlelll et al (1945), using the change in the concentration of VFA in the rumen contents as the criterion of absorption, found that the order of absorption of the three principal VFA was as suggested by Barcroft et al (1944a) when the rumen con tents were alkaline (pH 7.5)• However from rumen contents at a more acid reaction (pH 5.8) the higher homologues of the VFA were absorbed faster. Kiddle et al (1951) concluded that the higher homologues of the VFA were not absorbed prefer entially from rumen contents at an acid pH, but Gray et al (1951), Gray and Pilgrim (1951), Hungate et al (1961), Johnson (1951) and Pfander and Phillipson (1953) confirmed the conclusions of Danlelll et al (1945) and Gray (1947Gray ( , 1948.…”
Section: Structure Of the Rumensupporting
confidence: 76%
“…The main weakness of the technique is that it is conducted in vitro : confirmation of the validity of these results by in vivo techniques is still required. However, the in vivo data of Kiddle et al (1951) This difference may have been due to a greater permeability of the epithelium of the MHG calves or to some quite different factor such as greater blood flow. If permeability of the membrane was the important factor In the absorption studies, the differences in metabolic activity of the two tissues could be ascribed to the inability of the substrate to reach the site of metabolism rather than to the lower metabolic activity of the cells.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations